2005
DOI: 10.1039/b505424a
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of homogeneous Pd catalysts using superparamagnetic nanoparticles as novel soluble supports for Suzuki, Heck, and Sonogashira cross-coupling reactions

Abstract: Recycling of homogeneous catalysts could be achieved by using magnetic nanoparticles and solid-phase beads, but nanoparticle-supported catalysis proceeded much faster than its counterpart on resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(164 citation statements)
references
References 37 publications
3
153
0
2
Order By: Relevance
“…In particular the use of a soluble polymer support to immobilize N-heterocyclic carbene metal complexes has often been limited to one catalytic moiety per polymer chain. [50,[54][55][56][57] One exception to this is the work by Buchmeiser et al, whose group reported the functionalization of insoluble monolithic polymer discs with a variety of ruthenium catalysts using elegant post-polymerization functionalizations. [58] In this contribution, we report the synthesis of supported NHCs using poly(norbornene) as soluble polymer support.…”
Section: Introductionmentioning
confidence: 94%
“…In particular the use of a soluble polymer support to immobilize N-heterocyclic carbene metal complexes has often been limited to one catalytic moiety per polymer chain. [50,[54][55][56][57] One exception to this is the work by Buchmeiser et al, whose group reported the functionalization of insoluble monolithic polymer discs with a variety of ruthenium catalysts using elegant post-polymerization functionalizations. [58] In this contribution, we report the synthesis of supported NHCs using poly(norbornene) as soluble polymer support.…”
Section: Introductionmentioning
confidence: 94%
“…However, the magnetic nanoparticle supported nano-Pd(0) catalysts are more active than the magnetic nanoparticle supported homogeneous catalysts using N-heterocyclic carbene-coordinated Pd complexes. [21] The lower interaction chance of reactants in the threephase reaction mixture and relatively strong electrostatic interaction might contribute to lowering the efficiency of the catalyst. [29] In addition, after 3 runs, no obvious aggregation of Pd on the support surface to form visible nanoparticles was observed; only magnetic particle cores were observed using TEM with the oxidation state of Pd(0) confirmed by XPS analysis (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The main synthetic routes for the preparation of substituted dihydropyridines are Hantzsch method via the cyclocondensation of an aldehyde, β-ketoester and ammonia, 9 regioselective [4+2] cycloaddition of 1-aryl-4-phenyl-1-azadienes and allenic esters for the synthesis of N-aryl-1,4-DHPs, 10 and a multi-component reaction of alkyl amines, ethyl propiolate, and benzal- Magnetic nanoparticles show a great potential as catalysts because of their large surface area and the large ratio of atoms available at the surface to perform the chemical transformation of substrates. 17,18 However, the bare Fe 3 O 4 nanoparticles have high reactivity and easily undergo degradation upon direct exposure to certain environments, leading to poor stability and dispersity. Therefore, the surface of magnetic nanoparticles should be modified to improve the dispersity and biocompatibility, which could significantly facilitate its utilization.…”
Section: Introductionmentioning
confidence: 99%